RUSSIAN GUIDELINES FOR SUDDEN CARDIAC DEATH RISK ASSESSMENT AND PREVENTION (SECOND EDITION) – 2018. POCKET VERSION - Shlyakhto E. V.; Arutyunov G. P.; Belenkov Y. N.; Boytsov S. A. (Žurnal Grodnenskogo Gosudarstvennogo Medicinskogo Universiteta, 2019)
Cardiovascular mortality in Russia is one of the highest in the world reaching 614 deaths per 100,000 annually. The main causes of death from cardiovascular diseases are the progression of congestive heart failure (about half of all cases) and sudden cardiac death (the other half). Thus, we can assume that the incidence of sudden cardiac death in 2016 was no less than 300,000. In the abbreviated version of the National Recommendations in English, the principles of decision-making algorithms in various clinical situations are used.